The positions of Islamic jurists regarding the Umayyad state (41-132 AH / 661-749 AD) - "Extracted research" - مصطفى, شوان عثمان; بيروز, روشت جمال (Sulaimani Journal for Humanities, 2020)
Umayyad Caliphate state forms an important stage in the history of Islam . It is certain that in every historic period, states have their own political and ideological perspectives that have functioned as a method for the practice and legalization of their good and evil acts. The Umayyad State had their own method which stemmed from their belief in the supreme right to rule and prolong the practice of power as well as the exclusion of any opposing perspectives including even sacred religious texts. Many pious and truthfully religious figures have been either punished or exiled. To address this issue, the religious Imams were divided into two groups, one group legalized such method of the Umayyad Method and the other opposed it. The response of the Umayyad Caliphate state to these groups certainly differed. This paper focuses on demonstrating such different attitudes.